EVALUATION OF EFFECTS OF HEAVY METALS ON ABUNDANCE AND DIVERSITY OF SOIL MITES IN A TROPICAL LANDFILL (2016)
A study was carried out the Evaluation of Effects of Heavy Metals on Abundance and Diversity of Soil Mites in a tropical landfill in Ibadan from April to July 2003. Heavy metal sources from natural and the anthropogenic factors have increased their bioavailability and ecological impacts in the ecosystem. The objective of the study was to assess the impact of heavy metals on soil mites in a tropical landfill site in Ibadan. Five demarcated study plots at the landfill were randomly selected and marked out with a dimension of 10 metres by 10 metres with a Control site of the same dimension located at an elevated location about 100 metres away from the edge of the landfill. Soil samples at a depth of <10 cm were collected from the study plots using a hand trowel on a monthly basis. Buckard –Model of Berlesce-Tullgren funnel extractor was used to extract soil mites while the soil samples were acid-digested for heavy metal analyses using Shimadzu Atomic Absorption Spectrophotometer. With the exception Pb (1.99 ppm) at Plot 3, all the other mean heavy metals were below that of the Control Plot (6). Soil mite taxa had higher abundance and diversity at the Control plots than in the landfill. Heavy metals Cr, Ni, Zn, Cu, Mn and Fe concentrations in the study exceeded guideline limits set by the Federal Ministry of Environment (FEPA, 1992). The study concludes that the soil in Aba- Eku landfill in Ibadan is contaminated by heavy metals.